Pterostilbene Reduces Acetaminophen-Induced Liver Injury by Activating the Nrf2 Antioxidative Defense System via the AMPK/Akt/GSK3β Pathway - Xiaoye Fan; Lidong Wang; Jingbo Huang; Hongming Lv; Xuming Deng; Xinxin Ci (Cellular Physiology and Biochemistry, 2018)
Background/Aims: Pterostilbene (Pts), a natural dimethylated analog of resveratrol from blueberries, exerts antioxidative and anti-apoptotic effects in various diseases. This study aims to investigate the protective effects and mechanism of Pts against acetaminophen (APAP)-induced hepatotoxicity in vivo. Methods: C57BL/6 mice were treated with APAP or APAP+Pts. HepG2 cells were used to further explore the underlying mechanisms in vitro. The effects of Pts on hepatotoxicity were measured by commercial kits, Hematoxylin and Eosin (H&E) straining, TUNEL assay, Western blot analysis, and Flow cytometry assay. Results: In vivo, Pts treatment effectively protected against APAP-induced severe liver injury by decreasing the lethality rate, the serum alanine transaminase (ALT) and aspartate aminotransferase (AST) levels, liver histological injury, liver malondialdehyde (MDA) formation and myeloperoxidase (MPO) levels and by increasing liver glutathione (GSH) and superoxide dismutase (SOD) levels. Moreover, in Pts-treated mice, the nuclear factor-erythroid 2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) pathway was activated; however, APAP-induced c-Jun NH2-terminal kinase (JNK) activation, mitochondrial Bcl-2 Associated X Protein (Bax) translocation, apoptosis-inducing factor (AIF) levels and cytochrome c release were attenuated. In vitro, Pts was found to reverse hydrogen peroxide (H2O2) -induced cytotoxicity, reactive oxygen species (ROS) production and apoptosis that depended on Nrf2 activation. Moreover, Pts induced a dose-dependent increase in the phosphorylation of AMP-activated protein kinase (AMPK), serine/threonine kinase (Akt), and glycogen synthase kinase 3β (GSK3β) in HepG2 cells. Moreover, Pts protect against APAP or H2O2-induced toxicity were effectively attenuated or abolished in HepG2 Nrf2-/- cells and Nrf2-/- mice. Conclusion: Our data suggest that Pts protects against APAP-induced toxicity by activating Nrf2 via the AMPK/Akt/GSK3β pathway.